Identification of novel ‘inks’ for 3D printing using high throughput screening: bioresorbable photocurable polymers for controlled drug delivery - Louzao, Iria; Koch, Britta; Taresco, Vincenzo; Ruiz Cantu, Laura; Irvine, Derek J.; Roberts, Clive J.; Tuck, Christopher J.; Alexander, Cameron; Hague, Richard J.M.; Wildman, Ricky D.; Alexander, Morgan R. (American Chemical Society, 2018)
A robust discovery methodology is presented to identify novel biomaterials suitable for 3D printing. Currently the application of Additive Manufacturing is limited by the availability of functional inks, especially in the area of biomaterials-this method tackles this problem for the first time allowing hundreds of formulations to be readily assessed. Several functional properties, including the release of an antidepressive drug (paroxetine), cytotoxicity and printability are screened for 253 new ink formulations in a high-throughput format as well as mechanical properties. The selected candidates with the desirable properties are successfully scaled up using 3D printing into a range of objects architectures. A full drug release study, degradability and tensile modulus experiments are presented on a simple architecture to validating the suitability of this methodology to identify printable inks for 3D printing devices with bespoke properties.